Strengthening Academic Capacity Through International Teaching and Learning Exchange - Paula Dewanti; Atchima Manthon; Evi Triandini (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2026)
Building synergy and collaboration across communities is increasingly important for advancing the quality of higher education in today’s global era. This study explores a teaching and learning exchange program between the Institute of Technology and Business STIKOM Bali, Indonesia, and Valaya Alongkorn Rajabhat University under the Royal Patronage of Thailand. Designed with a participatory approach, the program brought together a range of activities, including guest lectures, teaching demonstrations, cultural immersion, and institutional visits. The experience not only enhanced technology-based teaching skills but also boosted students’ confidence in cross-cultural communication while opening opportunities for joint research and publications. These outcomes show that structured academic exchanges can create meaningful, long-term collaborations, enrich mutual understanding, and contribute significantly to strengthening international higher education networks.